Emerging responses to the COVID-19 crisis from family farming and the agroecology movement in Latin America – A rediscovery of food, farmers and collective action - Tittonell, Pablo Adrian; Fernandez, Manuela Teresa; El Mujtar, Veronica Andrea; Viegas Preiss, Potira; Sapura, Silvia; Laborda, Luciana; Mendonça, M.A.; Alvarez, Valeria Esther; Fernandes, G.B.; Petersen, Paulo F.; Cardoso, Irene María (Elsevier, 2021)
Este trabajo contó con la colaboración de 15 co-autores